Runic Lore and Legend: Wyrdstaves of Old Northumbria - Pennick, Nigel (Inner Traditions International, Limited, 2019)
Cover Image -- Title Page -- Epigraph -- Table of Contents -- Introduction -- Chapter 1. The Kingdom of Northumbria: A Brief History -- Chapter 2. The Spirit Landscape of Northumbria -- PAGAN CONTINUITY -- Chapter 3. Northumbrian Geomancy: The Year, Time, and Space -- THE EIGHT AIRTS -- SEASONS OF THE OLD NORTHUMBRIAN YEAR -- THE HALYMAN'S RIG -- THE YORK CORRIDOR OF SANCTITY -- Chapter 4. Runes and Consciousness: Weaving the Web of Wyrd -- Chapter 5. The Runes of Northumbria -- Chapter 6. The First Airt of the Northumbrian Runes -- FEOH-WEALTH -- UR-AUROCHS -- THORN-THORN -- OS-MOUTH -- RAD-RIDING -- CEN-TORCH -- GYFU-GIVING -- WYN-JOY -- Chapter 7. The Second Airt of the Northumbrian Runes -- HAEGL-HAIL -- NYD-NEED -- IS-ICE -- GER-SEASON -- EOH-YEW TREE -- PEORTH-A LIVELY TUNE -- EOLH-SECG-EELGRASS -- SIGEL-SUN -- Chapter 8. The Third Airt of the Northumbrian Runes -- TIR-THE GUIDING STAR -- BEORC-BIRCH TREE -- EH-HORSE -- MAN-HUMAN BEING -- LAGU-FLOWING WATER -- ING-ING -- ETHEL-HOME -- DAEG-DAY -- Chapter 9. The Fourth Airt of the Northumbrian Runes -- AC-OAK TREE -- AESC-ASH TREE -- YR-YEW BOW -- IOR-WATER BEAST -- EAR-DUST -- CWEORTH-RITUAL FIRE -- CALC-CUP -- STAN-STONE -- GAR-SPEAR -- Chapter 10. Runes in Magic and Encryption -- RUNES AND MAGIC -- Chapter 11. Magical Symbols and Artifacts of Old Northumbria -- HAEGL: NINE, THE MAGIC NUMBER OF THE NORTH -- RINGS OF POWER -- RUNIC CODES IN NORTHUMBRIA -- KNOTS, KNOTWORK, AND MEANINGFUL PATTERNS -- Chapter 12. Ing: Legendary and Magical History -- RAVENLANDEYE AND THE RITUAL SUICIDE OF EARL SIWARD -- OTHER SACRED BANNERS OF NORTHUMBRIA -- THE MAGIC OF LORD SOULIS -- DIVINE KINGSHIP AND ROYAL SAINTS -- SAINTS IN THE CULT OF BONES -- Chapter 13. Yr: The Outlaw Archers -- Chapter 14. Otherworldly Beings of the Northumbrian Landscape: Boggarts, Hobs, Brownies, and Bogeymen.